2020
DOI: 10.1074/jbc.ra120.015282
|View full text |Cite
|
Sign up to set email alerts
|

VBP1 modulates Wnt/β-catenin signaling by mediating the stability of the transcription factors TCF/LEFs

Abstract: The Wnt/β-catenin pathway is one of the major pathways that regulates embryonic development, adult homeostasis, and stem cell self-renewal. In this pathway, transcription factors T-cell factor/lymphoid enhancer factor (TCF/LEF), serve as a key switch to repress or activate Wnt target gene transcription by recruiting repressor molecules or interacting with the β-catenin effector, respectively. It has become evident that the protein stability of the TCF/LEF family members may play a critical role in controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…Because of the involvement of this pathway in various diseases, present efforts in the drug development field are aimed at identifying inhibitors of the b-catenin-TCF7L2 interactions 73 and the design of specific approaches targeting TCF7L2 stability. 74 Our findings here highlight a potential path for TCF7L2 as a target for intervention in individuals with TAA or for possible prevention in individuals at risk of TAA.…”
Section: Discussionmentioning
confidence: 60%
“…Because of the involvement of this pathway in various diseases, present efforts in the drug development field are aimed at identifying inhibitors of the b-catenin-TCF7L2 interactions 73 and the design of specific approaches targeting TCF7L2 stability. 74 Our findings here highlight a potential path for TCF7L2 as a target for intervention in individuals with TAA or for possible prevention in individuals at risk of TAA.…”
Section: Discussionmentioning
confidence: 60%
“…Phosphorylated Akt (p-Akt) can phosphorylate GSK3β and inhibit its kinase activity, leading to the inactivation of GSK3β [ 39 ]. Decreased GSK3β alleviates restraint on β-catenin [ 40 ], contributing to the accumulated β-catenin entry into the nucleus to activate gene transcription and interacts with TCF/LEF and ultimately triggers the transcription of target genes including snail [ 41 , 42 ]. As a direct downstream gene of snail, the expression of epithelial biomarker E-cadherin was significantly downregulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that VBP1 did not regulate HIF-1α protein synthesis. We and others have shown that VBP1 induced ubiquitination of the HIF-1α protein in cultured cells ( 29 , 30 ). Surprisingly, MG132 (a proteasomal inhibitor) treatment only partly rescued VBP1-mediated HIF-1α degradation ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, VBP1 facilitates proteasomal and autophagy-mediated degradation of hMSH4 ( 28 ). We recently reported that VBP1 modulates Wnt/β-catenin signaling by mediating the stability of TCF/LEFs ( 29 ). A recent study reported that VBP1 facilitates HIF-1α degradation by stabilizing pVHL ( 30 ).…”
mentioning
confidence: 99%